Analisis Kesinambungan, Inovasi, dan Sintesis Teologi Transisional Terhadap Yehezkiel 37:1-14 - Vivi Salmi (Sekolah Tinggi Teologi Bethel Ambon, 2026)
This article analyzes Ezekiel 37:1-14 as a transitional text that bridges classical prophetic tradition with the apocalyptic horizon in the Old Testament canon. The research employs a theological-biblical approach through a library research methodology. Through a three-dimensional analysis encompassing continuity, innovation, and synthesis, this article argues that the vision of the dry bones valley is not merely a contextual response to the Babylonian exile trauma, but also a symbolic breakthrough that laid the foundation for the development of resurrection eschatology in the New Testament. Continuity with prophetic tradition is maintained through prophetic formulas and the orientation toward national restoration. Innovation is evident in the use of mass resurrection symbolism and the function of the Spirit as a source of eschatological life. The synthesis of both dimensions positions Ezekiel 37 as a theological bridge between classical prophecy and apocalyptic literature. These findings carry hermeneutical implications for intertextual readings between the Old and New Testaments.